VALORISASI TANAMAN EKOR KUCING (TYPHA LATIFOLIA L.) HASIL FITOREMEDIASI LIMBAH ELECTROPLATING MENJADI HIDROLISAT GULA PEREDUKSI MELALUI PROSES HIDROLISIS OLEH JAMUR ASPERGILLUS ORYZAE - Baihaqi, Misbah
The increasing nickel production in Indonesia is followed by a rise in industrial waste containing nickel, such as electroplating waste. To address the environmental pollution challenges posed by heavy metal-containing waste, including nickel, efforts have been made to reduce contaminants through phytoremediation processes. Phytoremediation using cattail (Typha latifolia) is a remediation approach chosen due to its known high tolerance to heavy metals. However, the biomass of cattail resulting from phytoremediation needs to be converted into a bioproduct to avoid the generation of new waste caused by the phytoremediation. This study aims to evaluate the ability of cattail to remediate electroplating waste in a vertical subsurface constructed wetland, with variations in concentration levels of control, 385 ppm, and 1100 ppm. Additionally, it aims to utilize the biomass of T. latifolia resulting from phytoremediation to produce reducing sugars through hydrolysis by using Aspergillus oryzae fungus. The parameters observed for the wastewater quality include pH, Total Dissolved Solids (TDS), Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and the percentage removal of nickel in the wastewater. Parameters observed for the cattail include Relative Growth Rate (RGR), Bioconcentration Factor (BCF), and Translocation Factor (TF). Furthermore, the content of reducing sugars, which include glucose, xylose, mannose, and arabinose, generated from the hydrolysis of T. latifolia resulting from phytoremediation, were measured. The research findings indicate that T. latifolia plants can remediate electroplating waste containing nickel up to 1100 ppm, with a plant RGR value of 0.0018 kg/ day; a reduction in TDS of up to 67.18%; a decrease in BOD and COD levels of 67.16% and 66.67%, respectively; and a TF value of 0.238. T. latifolia plants can accumulate heavy metal nickel in their roots up to 47 ppm, with a percentage removal of 99.99%. Moreover, the hydrolysis of the biomass from the control, 385 ppm, and 1100 ppm treatments using Aspergillus oryzae resulted in contents of reducing sugars of 0.338, 0.213, and 0.195 mg/g dry biomass weight, respectively. The resulting reducing sugars have the potential to be used as raw materials in the chemical industry or as feedstock for bioethanol production.